1992
DOI: 10.1002/pca.2800030108
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for the isolation and identification of coumarins with calcium antagonistic properties from the roots of Angelica archangelica

Abstract: Fifteen coumarins, 2′‐angeloyl‐3′‐isovaleryl vaginate (4), archangelicin (3), oxypeucedanin hydrate (8), bergapten (5), byakangelicin angelate (15), imperatorin (11), isoimperatorin (6), isopimpinellin (13), 8‐[2‐(3‐methylbutroxy)‐3‐hydroxy‐3‐methylbutoxy]psoralen (12), osthol (1), ostruthol (9), oxypeucedanin (7), phellopterin (14), psoralen (2) and xanthotoxin (10), have been isolated from a chloroform extract of the roots of Angelica archangelica L. subsp. archangelica (Apiaceae). 2, 4, 12, and 15 are repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…500-fold more effective in inhibiting the 45 Ca 2 + entry in GH 4 C 1 cells (Table 2, IC 50 values 0.007 and 3.4 AM, respectively). The IC 50 value obtained for verapamil is in accordance with our previous results and literature data on this inhibitor (4.2 AM [13], 4.1 AM [10], and 1 AM [26]). The dose -response curves for these compounds are presented in Fig.…”
Section: Validation Of the Assay With Model Compoundssupporting
confidence: 94%
“…500-fold more effective in inhibiting the 45 Ca 2 + entry in GH 4 C 1 cells (Table 2, IC 50 values 0.007 and 3.4 AM, respectively). The IC 50 value obtained for verapamil is in accordance with our previous results and literature data on this inhibitor (4.2 AM [13], 4.1 AM [10], and 1 AM [26]). The dose -response curves for these compounds are presented in Fig.…”
Section: Validation Of the Assay With Model Compoundssupporting
confidence: 94%
“…Subsequently, fifteen furocoumarins were isolated and tested. The most potent calcium uptake antagonist was archangelicin (Härmälä et al, 1992). The anticonvulsive activity of imperatorin from the fruits of A. archangelica was tested in mice, where the threshold of MES induced seizures was measured after 15, 30, 60 and 120 min.…”
Section: Resultsmentioning
confidence: 99%
“…Glowniak et al [37] demonstrated that the application of mixed binary or ternary solvents of dichloromethane, chloroform, trichloroethylene, ether, petrol, and tetrachloromethane leads to a significant increase in the extraction efficiency. Härmälä et al [38] investigated 20 organic solvents to apply them in the extraction of coumarins from the root of A. archangelica. Physicochemical parameters, such as density, viscosity, surface tension, and number of carbon atoms in a molecule, were compared in relation to concentrations of polar and no polar substances obtained in extraction processes.…”
Section: Extraction From Plant Materialsmentioning
confidence: 99%
“…The fluid is characterized by a high diffusion coefficient, low viscosity and density, and lack of surface tension. The fluid has very good penetration and the ability to dissolve the substances in this matrix [38,41].…”
Section: Extraction From Plant Materialsmentioning
confidence: 99%